Advanced Manufacturing Technologies Modern Machining, Advanced Joining, Sustainable Manufacturing - Gupta, Kapil (Materials Forming, Machining and Tribology, 2017)
This book provides details and collective information on working principle, process mechanism, salient features, and unique applications of various advanced manufacturing techniques and processes belong. The book is divided in three sessions covering modern machining methods, advanced repair and joining techniques and, finally, sustainable manufacturing. The latest trends and research aspects of those fields are highlighted.